Assessing the importance of environmental factors to phytoliths of Phragmites communis in north-eastern China. (October 2016) - Liu, Lidan; Jie, Dongmei; Liu, Hongyan; Gao, Guizai; Gao, Zhuo; Li, Dehui; Li, Nannan; Guo, Jixun; Qiao, Zhihe
Highlights: We assess the relation between phytolith and climate, edaphic factor, micro terrain. Phytolith are influenced largely by the average annual temperature and precipitation. Short-cell phytolith concentrations are closely linked to average annual temperature. Concentrations of non-short-cell phytoliths are more sensitive to water status. Abstract: Phytoliths have proved to be reliable indicators of environmental conditions both at present and in the past, and can provide evidence for the distribution of taxa or vegetation. Understanding the environmental significance of phytoliths within plants helps in drawing more reliable inferences about palaeovegetation and in reconstructing the palaeo-environment. The present study examined the relationship between phytoliths and environmental factors to assess the environmental significance of different types of phytoliths. Phytoliths were extracted from Phragmites communis growing in xerophytic and aquatic habitats at twelve sampling sites in north-eastern China and their implications for the environment were assessed using quantitative data mainly including phytolith concentration and environmental factors and statistical analyses. Principal component analysis (PCA) of several environmental factors (including the climate, micro terrain, and the physicochemical properties of soils) revealed that other factors being constant, P. communis phytolith concentrations were influenced largely by the average annual temperature and precipitation. Orthogonal experiment analysis and three-way analyses of variance of the concentrations confirmed the reliability of the results of the PCA. More specifically, the concentrations of the saddle and rondel types of phytoliths (the short-cell phytoliths) were closely linked to the average annual temperature whereas those of the elongate, lanceolate, and bulliform phytoliths (the non-short-cell phytoliths) were more sensitive to the variations in water status. The results contribute to further confirming the major environmental implications of phytoliths and, in turn, providing a reference for growth and development of wetland plants. Our findings also provide critical information that could help managers and policymakers assess and modify ecological restoration practices.